Nature, prevalence and determinants of mental health problems experienced by adolescents in south Asia: a systematic reviewResearch in context - Chethana Mudunna; Medhavi Weerasinghe; Thach Tran; Josefine Antoniades; Lorena Romero; Miyuru Chandradasa; Jane Fisher (The Lancet Regional Health - Southeast Asia)
Summary: Background: Adolescence is a sensitive phase of human development where individuals, aged 10–19 years, are particularly vulnerable to developing mental health problems (MHPs). South Asia, home to 24% of the world's population, is mostly comprised of low- and middle-income countries (LMIC). Most of the world's young people live in LMICs. This systematic review aims to assess the available evidence on the nature, prevalence and determinants of MHPs experienced by adolescents in south Asia. Methods: Following PRISMA guidelines, searches were conducted in four online databases (Ovid Medline, Ovid EMBASE, Ovid Global Health, Ovid PsycInfo), titles, abstracts, and full-texts were screened, data extracted and quality assessed. Extracted data were categorised into school-based studies (SBS) and non-school-based studies (NSBS). Data were further stratified according to country, MHPs and narratively synthesised. Findings: Of the 5847 records identified in the searches, 117 met inclusion criteria. Most (n = 87) were SBS. Key MHPs reported across countries include anxiety disorders and depression. Wide ranges of prevalence rates were reported for anxiety in Indian SBS (1.5–81.6%) and NSBS (1.8–88.1%), and for depression, Pakistani SBS (21–79%) and Indian NSBS (0.4–98.5%). Determinants include individual characteristics; violent victimisation; poor family/home/school environment/peer relationships; already experiencing MHPs and substance use/abuse. Increased physical activity, adequate nutrition, safe/positive homes/family environment, being unmarried females, higher maternal education, peer support/friendship, higher education level and engaging in extra-curricular activities were protective of mental well-being. Interpretation: Prevalence of MHPs among south Asian adolescents appears high. Determinants include social, cultural, environmental and socioeconomic factors often beyond individual control. Mental health policies and programs and research appropriate to the cultural context, that address social determinants of MHPs and evidence gaps, are needed to tackle the significant mental health burden among south Asian adolescents. Funding: Authors CM and MW are supported by a Monash University Research Training Program Scholarship. JF is supported by the Finkel Professorial Fellowship funded by the Finkel Family Foundation.